2011
DOI: 10.3109/17435390.2011.611915
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary exposure of rats to ultrafine titanium dioxide enhances cardiac protein phosphorylation and substance P synthesis in nodose ganglia

Abstract: The inhalation of engineered nanoparticles stimulates the development of atherosclerosis and impairs vascular function. However, the cardiac effects of inhaled engineered nanoparticles are unknown. Here, we investigate the effects of ultrafine titanium dioxide (UFTiO(2)) on the heart, and we define the possible mechanisms underlying the measured effects. Pulmonary exposure of rats to UFTiO(2) increased the phosphorylation levels of p38 mitogen-activated protein kinase and cardiac troponin I, but not Akt, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 48 publications
(59 reference statements)
2
26
0
Order By: Relevance
“…Secondly, translocation or direct interaction may initiate redox chemistry within the vasculature, as these ENM may be manufactured from or coated with a variety of highly reactive materials capable of producing reactive species or reducing antioxidant competence within a physiological environment [16,51,52]. Lastly, the neural route may stimulate sensory neurons leading to altered afferent and efferent signaling patterns ultimately effecting the maintenance of smooth muscle tone [53,54]. These pathways are not isolated or independent of each other and they may operate in conjunction with the other routes.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, translocation or direct interaction may initiate redox chemistry within the vasculature, as these ENM may be manufactured from or coated with a variety of highly reactive materials capable of producing reactive species or reducing antioxidant competence within a physiological environment [16,51,52]. Lastly, the neural route may stimulate sensory neurons leading to altered afferent and efferent signaling patterns ultimately effecting the maintenance of smooth muscle tone [53,54]. These pathways are not isolated or independent of each other and they may operate in conjunction with the other routes.…”
Section: Resultsmentioning
confidence: 99%
“…29 Similar microvascular dysfunction has been reported after inhalation of nano-titanium dioxide and has been associated with stimulation of sensory neurons from the lung and enhanced sympathetic input at the systemic arterioles. 30,31 Aspiration of MWCNTs has also been reported to increase baroreflex activity in rats. 32,33 In addition, Erdely et al 34 reported transient elevation of blood inflammatory mediators after aspiration of MWCNTs, which may mediate this systemic microvascular response.…”
Section: Cardiovascular Responsesmentioning
confidence: 99%
“…Cardiac inflammation has been shown to occur following exposure to TiO 2 UFP without quantifiable increases in circulating pro-inflammatory cytokines raising further questions on the role of circulating mediators versus direct translocation (Kan et al 2011). It is plausible that low levels of constant circulating inflammatory cytokines over an extended amount of time could be sufficient for the development of chronic cardiovascular diseases.…”
Section: Pulmonary-derived Mediator Release and Systemic Effectsmentioning
confidence: 99%